'She Felt Strongly the Injury to Her Affections': Breach of Promise of Marriage and the Medicalization of Heartbreak in Early Twentieth-Century Australia. Issue 2 (4th May 2017) - Simmonds, Alecia
ABSTRACT: This paper examines the relationship between law, medical knowledge and romantic suffering in early twentieth-century Australia. Drawing upon a sample of breach of promise of marriage actions from 1824 to 1930, it argues that where the plaintiff's pain was largely presumed in the nineteenth century, by the twentieth century mastering the language and performance of anguish became crucial to legal success. The less that women suffered socially from romantic disappointment, the more they sought to prove it in court. Women dressed the lesions of their hearts in the disinterested language of medicine and borrowed psychological categories of trauma from victims of war and railway injuries. Heartbreak was thus legitimized as a species of pain by a convergence of law, medicine and women's audacity to take their feelings seriously. The court's response to these new bodily articulations of suffering provides a counter-history to the usual tale of law's preference for the tangible over the intangible. Somatic injury was relegated to special damages, determined by the evidence of doctors and with less lucrative compensation, while emotional injury occupied the dominant, more profitable category of general damages. The history of heartbreak thus demonstrates the historical contingency of legal hostility to emotional injury.